2023
DOI: 10.3390/cancers15133473
|View full text |Cite
|
Sign up to set email alerts
|

Lactate as Key Metabolite in Prostate Cancer Progression: What Are the Clinical Implications?

Abstract: Advanced prostate cancer represents the fifth leading cause of cancer death in men worldwide. Although androgen-receptor signaling is the major driver of the disease, evidence is accumulating that disease progression is supported by substantial metabolic changes. Alterations in de novo lipogenesis and fatty acid catabolism are consistently reported during prostate cancer development and progression in association with androgen-receptor signaling. Therefore, the term “lipogenic phenotype” is frequently used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 147 publications
0
5
0
Order By: Relevance
“…In advanced stages of the disease, PC cells display an overexpression of glucose transporters and key glycolytic enzymes [ 11 ], leading to increased glucose consumption and lactate release [ 21 ]. The elevated lactate produced in hypoxic tumor areas is secreted into the extracellular environment [ 22 ], resulting in a high concentration of serum lactate (approximately 40 mM) observed in the serum of various cancer patients compared to the lactate concentration in healthy tissue and serum (1.5 to 3 mM) [ 23 ]. We observed elevated serum lactate levels in mCRPC patients compared to the BPH group, which aligns with previously reported findings in PC tissues [ 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In advanced stages of the disease, PC cells display an overexpression of glucose transporters and key glycolytic enzymes [ 11 ], leading to increased glucose consumption and lactate release [ 21 ]. The elevated lactate produced in hypoxic tumor areas is secreted into the extracellular environment [ 22 ], resulting in a high concentration of serum lactate (approximately 40 mM) observed in the serum of various cancer patients compared to the lactate concentration in healthy tissue and serum (1.5 to 3 mM) [ 23 ]. We observed elevated serum lactate levels in mCRPC patients compared to the BPH group, which aligns with previously reported findings in PC tissues [ 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…We observed elevated serum lactate levels in mCRPC patients compared to the BPH group, which aligns with previously reported findings in PC tissues [ 24 , 25 , 26 ]. We propose that cells in the tumor microenvironment produce lactate, serving as the source of increased blood serum lactate in patients with PC, and it may contribute to tumor cell invasion, metastasis, and immunosuppression [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The raw data were first converted to mzXML format by MSConvert in the Prote-oWizard software package (v3.0.8789) and processed using R XCMS (v3.12.0) for feature detection [21,22], retention time correction, and alignment. The key parameter settings were set as follows: ppm = 15, peak width =c (5,30), mz diff = 0.01, and method = centWave. The batch effect was then eliminated by correcting the data based on the quality control (QC) samples.…”
Section: Data Preprocessingmentioning
confidence: 99%
“…From Figure 7 depicting the Central carbon metabolism in cancer pathway, it is evident that glucose in the fermentation broth is consumed due to the metabolic requirements for growth, facilitated by the glucose transporter CLUT1/2, leading to a reduction From Figure 7 depicting the Central carbon metabolism in cancer pathway, it is evident that glucose in the fermentation broth is consumed due to the metabolic requirements for growth, facilitated by the glucose transporter CLUT1/2, leading to a reduction in intracellular glucose levels. P53 has immense potential in inhibiting tumors by controlling cell senescence, apoptosis, and DNA repair, and is a common tumor suppressor gene in human tumors, regarded as a "star molecule" in oncology [30]. P53 indirectly inhibits glucose conversion to G6P, thereby suppressing the glycolytic pathway [31].…”
Section: Differential Pathway Enrichment Analysismentioning
confidence: 99%
“…Metabolic reprogramming constitutes a hallmark of cancer [8]. In PC, metabolic reprogramming is significantly associated with disease progression to CRPC [9,10]. Previous studies have shown that patients with CRPC exhibited higher levels of glycolysis and oxidative phosphorylation (OXPHOS) compared with those having primary PC tumors [9].…”
Section: Introductionmentioning
confidence: 99%